Exploitable wind power potential in Turkey with technological advancement and resulting environmental-economic aspects - KURŞUN, BERRİN (My University, 2023)
This work\"s focus is determining how the improvements in wind power technology alter current onshore wind power potential and exploitable electrical energy in Turkey. Then, consequent environmental and economic benefits through substitution of imported hard coal, natural gas and local lignite resources in the Turkish electricity mix have been analyzed. Lack of potential, environmental and economic data kept offshore wind calculations out of the scope of this work. Increasing hub height and power coefficient due to better blade designs of wind turbines can increase 114 thousand MW of onshore wind power potential at 50 m up to 418 thousand MW at 300 m. Consequent wind electricity generation can change in the range of 2.3 x 10(5)-1.95 x 10(6) GWh. Acknowledging several different conditions operating wind turbines can be subject to and that the whole capacity may not be used, mean value of 1.09 x 10(6) GWh wind electricity generation is assessed as the limit providable to the Turkish electricity grid. Installable wind power capacity (IWPC) and electricity generation potential (EGP) are both most sensitive to the changes in spacing followed by CP and aging. The level of sensitivity increases at higher hub heights for both IWPC and EGP. Environmentally, substitution of lignite and after 2040 hard coal and lignite by wind power is the most feasible option in improving environmental performance of Turkish electricity mix compared to sole substitution of hard coal, natural gas or lignite. In 2040, wind can replace all lignite hence in the years following 2040, wind can substitute lignite and a second fossil resource. Economically, hard coal and natural gas substitution result in 10.85 billion $ and 7.93 billion $ gain from 2021to 2050. Local job creation and carbon tax mechanisms to be employed in favor of wind power can create additional economic and social benefits for the country.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; ENERJİ VE YAKITLAR; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERGY & FUELS; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences